Proposals for Second Five Year Plan Tourism Sector Government of Rajasthan - Planning Commission (Planning Commission, 1955)
The tourist traffic is growing into on important industry in a Large number of countries all over the world. It has been established that tourism can make a great contribution to the economy of a country. In Rajas than there is a great scope for the development of the industry The splendor which is Rajasthan abound a bounds with magnificent edifices, rich historical moments, and places of natural beauty which attract tourists from far and wide all the year round.
Government of Rajasthan Planning Department